A Analysis Of Work Motivation On Employee Performance At PT. Surya Langgeng Sejahtera Kalumpang District, Hulu Sungai Selatan District, South Kalimatan Province - Amalia Fauziah Hulwani (Citakonsultindo, 2023)
Research purposes is For know Motivation Work On Employee Performance at PT. Surya Langgeng Sejahtera District Kalumpang , Hulu Sungai Selatan Regency , Province Southern Kalimantan . Type of method study is study descriptive and qualitative , data analysis methods used is analysis linear regression with using SPSS 20. Data source obtained with using primary and secondary data where the primary data was obtained from questionnaire that has been shared to respondents . Research result state that motivation influential to performance employee At PT. Surya Langgeng Sejahtera District Kalumpang , Hulu Sungai Selatan Regency , Province Sentence South .